Phloretic acid requires the insulin/IGF-1 pathway and autophagy to enhance stress resistance and extend the lifespan of Caenorhabditis elegans - Li, Bo; Dong, Li; Meng, Wei; Xiong, Shi-Ying; Wu, Gui-Sheng; Ma, Wen-Zhe; Luo, Huai-Rong (Frontiers in Pharmacology, 2024)
In humans, aging is associated with increased susceptibility to most age-related diseases. Phloretic acid (PA), a naturally occurring compound found in Ginkgo biloba and Asparagus, exhibits potential as an anti-aging agent and possesses antioxidant, anti-inflammatory, and immunomodulatory properties. In this study, we investigated the effects of dietary supplementation with PA on longevity and stress response using Caenorhabditis elegans (C.elegans) as a model organism. Our findings demonstrated that PA dose-dependently extended the C.elegans lifespan, with 200 μM PA showing the greatest effect and increased the C.elegans lifespan by approximately 16.7%. PA enhanced motility and the pharyngeal pumping rate in senescent C. elegans while reducing the accumulation of aging pigments. Further investigations revealed that daf-16, skn-1, and hsf-1 were required for mediating the lifespan extension effect of PA in C.elegans since its impact was suppressed in mutant strains lacking these genes. This suggests that PA activates these genes, leading to the upregulation of downstream genes involved in stress response and senescence regulation pathways. Furthermore, PA did not extend the lifespan of the RNAi atg-18 and RNAi bec-1, but it attenuated SQST-1 accumulation, augmented autophagosome expression, upregulated autophagy-related gene expression, and downregulated S6K protein levels. These findings suggest that the potential life-extending effect of PA also involves the modulation of the autophagy pathway. These findings highlight the promising anti-aging effects of PA and warrant further investigation into its pharmacological mechanism and medicinal development prospects.